2006
DOI: 10.1038/sj.npp.1301219
|View full text |Cite
|
Sign up to set email alerts
|

Brain Morphometry and Cognitive Performance in Detoxified Alcohol-Dependents with Preserved Psychosocial Functioning

Abstract: The extent of structural brain damage and related cognitive deficits has been little described in alcohol-dependent individuals with preserved social functioning. Thus, we investigated the relationship between regional alterations, executive performance, and drinking history. Volumes of gray and white matter were assessed using magnetic resonance imaging voxel-based morphometry in healthy men and in detoxified alcohol-dependent men with good psychosocial functioning. Their executive performance was assessed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
295
1
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 368 publications
(335 citation statements)
references
References 66 publications
22
295
1
10
Order By: Relevance
“…Previous investigations on alcoholism have provided evidence of an association between white matter structure in the corpus callosum and certain components of executive functions, eg attention skills and inhibitory control (Schulte et al, 2006). In our own recent study, decreased white matter volume in the midbrain of alcoholdependent subjects was related to impaired performance in two executive tasks: the Trail-Making Test part-B (TMT-B) and the WAIS letter-number sequencing test (LNS; Chanraud et al, 2007). Both tasks invoke cognitive flexibility, a component of executive functions, which is known to influence treatment outcome (Goldman, 1990) and experience-dependent recovery (Roehrich and Goldman, 1993) in chronic alcoholism.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations on alcoholism have provided evidence of an association between white matter structure in the corpus callosum and certain components of executive functions, eg attention skills and inhibitory control (Schulte et al, 2006). In our own recent study, decreased white matter volume in the midbrain of alcoholdependent subjects was related to impaired performance in two executive tasks: the Trail-Making Test part-B (TMT-B) and the WAIS letter-number sequencing test (LNS; Chanraud et al, 2007). Both tasks invoke cognitive flexibility, a component of executive functions, which is known to influence treatment outcome (Goldman, 1990) and experience-dependent recovery (Roehrich and Goldman, 1993) in chronic alcoholism.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently reported that alcohol has neurotoxic effects on cerbellum as measured by regionof-interest volumetry and VBM approach (Chanraud et al, 2007;Maschke et al, 2005;Sullivan et al, 2000). Accordingly, we instituted strict inclusionary/exclusionary criteria to minimize the effects of the alcohol confound in this study.…”
Section: Comorbid Alcohol and Nicotine Abusementioning
confidence: 99%
“…Moreover, the age subjects reported their first drink and frequency of drinking to "get high" were associated with left-frontal slow alpha electroencephalograph activity. Similarly, Chanraud et al, (2007) reported the age of first drinking was linked with decreased gray matter volume in frontal cortex, cerebellum, and pons using Magnetic Resonance Imaging suggesting that these regions may be more vulnerable to the neurotoxic effects of alcohol during adolescence.…”
Section: Executive Dysfunction and Vulnerability To Alcohol Dependencementioning
confidence: 99%